Select the simplified expression for 4(x - 4) - 2(x - 3) + 3x.

Question

Asked 5/24/2013 2:16:08 AM

Updated 8/10/2014 5:50:50 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [8/10/2014 5:50:45 PM]

twistedechoes|Points 46|

Question

Asked 5/24/2013 2:16:08 AM

Updated 8/10/2014 5:50:50 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by alfred123 [8/10/2014 5:50:45 PM]

Rating

3

4(x - 4) - 2(x - 3) + 3x

= 4x - 16 - 2x + 6 + 3x

= 5x - 10

= 4x - 16 - 2x + 6 + 3x

= 5x - 10

Added 8/10/2014 5:50:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/10/2014 5:56:48 PM]

Solve.
4x + 9 = 8

Question

Expert Answered

Updated 233 days ago|12/1/2017 6:05:06 AM

1 Answer/Comment

4x + 9 = 8

4x = 8 - 9

4x = -1

x = -1/4

4x = 8 - 9

4x = -1

x = -1/4

Added 233 days ago|12/1/2017 6:05:06 AM

This answer has been confirmed as correct and helpful.

Express 79000000 in scientific notation.

Question

Not Answered

Updated 168 days ago|2/4/2018 8:56:40 AM

1 Answer/Comment

27,106,655

questions answered

There are no comments.